Adaptive control for a motion mechanism with pneumatic artificial muscles subject to dead-zones - Zhao, Ling; Cheng, Haiyan; Zhang, Jinhui; Xia, Yuanqing (Mechanical systems and signal processing, 2021)
•Dead-zones of pneumatic artificial muscles are considered in system modeling.•Total disturbances are estimated by a nonlinear extended state observer.•An adaptive control law is proposed to handle dead-zones parameters. This paper proposes an adaptive control method for a motion mechanism of pneumatic artificial muscles based on a nonlinear extended state observer. The motion mechanism of pneumatic artificial muscles is modeled as a dynamic nonlinear system. Dead-zones of the pneumatic artificial muscles are considered in modeling the dynamic nonlinear system. The nonlinear extended state observer is designed to estimate total disturbances for the dynamic nonlinear system. Moreover, the dead-zones are dealt with by an adaptive control law for the dynamic nonlinear system. The effectiveness of the proposed adaptive control method is proved by angle tracking control experiments.